2021
DOI: 10.7150/ijms.46421
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5-related cell death patterns

Abstract: With the increasingly serious problem of environmental pollution, the health problems caused by PM2.5 are gradually coming into our line of sight. Previous researches have indicated that air pollution is nearly related to various diseases, but few studies have focused on the exact function mediated by particulate matter less than 2.5 (PM2.5) in these diseases. PM2.5 is known to induce multiple ways of cell death, including autophagy, necrosis, apoptosis, pyroptosis and ferroptosis. Therefore, it is of much imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Ferroptosis is a newly identified programed cell death that characterized by abnormal iron metabolism, lipid metabolism, oxidative stress, and glutathione (GSH) [11]. Increasing evidence has demonstrated that ferroptosis is correlated with various diseases, including cancer, cardiovascular diseases, and neurodegenerative diseases [12][13][14]. Besides, previous study has identified that ferroptosis participate in the progression of lung injury [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a newly identified programed cell death that characterized by abnormal iron metabolism, lipid metabolism, oxidative stress, and glutathione (GSH) [11]. Increasing evidence has demonstrated that ferroptosis is correlated with various diseases, including cancer, cardiovascular diseases, and neurodegenerative diseases [12][13][14]. Besides, previous study has identified that ferroptosis participate in the progression of lung injury [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Few new studies have focused on the function of particulate matter on men. Based on these research studies, autophagy, necrosis, apoptosis, pyroptosis, and ferroptosis are the most well-known side effects of PM 2.5 [51]. In our study, the average number of IHD was 27.92 cases.…”
Section: The Estimate Of the Ihd Incidence Related To Pm 25 Concentra...supporting
confidence: 49%
“…Clarifying its underlying mechanism is essential to determine effective prevention and treatment strategies. Based on previous reports, the mechanism of PM 2.5 -induced lung damage is complex, including oxidative stress, inflammation, apoptosis, necrosis, and autophagy, and all forms not only occur simultaneously but also overlap and crosstalk with one another. Some studies have pointed out the anti-inflammatory and antioxidant effects of Ses. , Ses could reduce carrageenan-induced lung inflammation, and its anti-inflammatory mechanism was proven to be related with the inhibition of the NF-κB pathway, upregulation of A20 and reduction of polymorphonuclear neutrophil infiltration . In this research, we unveiled, for the first time, that Ses pretreatment could significantly ameliorate PM 2.5 -induced lung toxicity.…”
Section: Discussionmentioning
confidence: 68%